Answer:
5x2−9x=7 (Option B)
Step-by-step explanation:
this is correct 100%
Answer:
BHF
Step-by-step explanation:
Definition of inscribed
We must follow order of operations rules (PEMDAS) here: exponentiation first, followed by multiplication and division, followed by addition and subtraction.
Thus, -2^2-3(-2)+1 becomes:
-[4] + 6 + 1 = 2 + 1 = 3 (answer)
Answer: f(x)/g(x) = 3x^2 + 6x - 2 - 12/3x+1
Step-by-step explanation:
The first function is f(x) = 9x^3+21x^2-14
The second function is g(x) = 3x+1
f(x)/g(x = 9x^3+21x^2-14/3x+1
We perform the long division as shown in the attachment to obtain the quotient as: Q(x) = 3x^2+6x - 2 and remainder R = -12
Therefore f(x)/g(x) = 3x^2 + 6x - 2 - 12/3x-1
Where x does not = -1/3
14%=56%
56%=56/100=0.56
14=0.56 of all
14=0.56 times all
divide both sides by 0.56
25=all
25 performers total